Sobre circunstâncias e experiências de projecto: a matéria do projetar - Ana Rita Correia Gomes (2016)
This work explores the process of developing a project, seeking an understanding on what is the essence of it. Therefore, this understanding is built on the analysis of some conditions of the development of the project. They are identified from opportunities, experiences and project references. The decision to explore the project through experiences and personal references is due to the fact that these represent some of the main themes that determine the action of the project. The situations chosen represent key moments to building the idea of what is the action of the project. Competition entries, internship experiences in offices in Paris and the project Fun Palace from Cedric Price are the three main experiences showcased in the work. They are examples of project opportunities, professional experiences and references of a personal view on the project. These circumstances are divided into the following themes: liberation, innovation, experimenting, representation, organization, questioning, interpretation and response. Each of these themes has its origin in a specific experience, referring to the creative process or the context that determines the path followed by the project. The themes are then organized into to main subjects: creativity and context. Given the fact that the work tries to understand the project through several independent topics, these no longer need to be read linearly or with any other specific type of sequence. They are merely autonomous perspectives on the same subject. They are ways of understanding the project.